Entwicklung von konsumbasierten Landnutzungsindikatoren. Synthesebericht. - (:unkn) unknown (My University, 2017)
Dieser Synthesebericht präsentiert die Schlüsselergebnisse aus dem UFOPLAN-Vorhaben zu Landnutzungsindikatoren, mit dem das Umweltbundesamt das Ziel verfolgte, Indikatoren aus einer Konsumperspektive weiter zu entwickeln, um damit die Deutsche Nachhaltigkeitsstrategie zu unterstützen. Nach einem strukturierten Überblick über bestehende Berechnungsmethoden des Flächenfußabdrucks werden die technischen und strukturellen Eigenschaften sowie ihre Vor- und Nachteile beschrieben. Dies führt zur Spezifizierung einer hybriden Methode als bevorzugten Berechnungszugang. Im zweiten Teil wird die entwickelte innovative, hybride Methode zur Berechnung des Flächenfußabdrucks vorgestellt. Weiterhin bietet der Bericht einen Überblick über bestehende Indikatorensysteme zur Abbildung der Umweltfolgen von Landnutzung und diskutiert, in wie weit diese flächenbasierten Fußabdruckindikatoren in komplementärer Form ergänzt werden können. Der Synthesebericht schließt mit einem Überblick über jene Themen ab, die in zukünftigen Arbeiten adressiert werden sollten.

With this UFOPLAN project on land use indicators, the German Federal Environment Agency aimed at further developing indicators from a consumption perspective in support of Germany s sustainabil-ity strategy, covering both area-based and impact-oriented land footprint indicators. The project also aimed at calculating selected land footprint indicators for Germany and the EU. These indicators should provide an improved understanding of the global teleconnections of consumption and land use relevant for policy making towards achieving sustainable land use. This synthesis report presents the key results from this project. First, we present a structured overview of existing approaches for estimating land footprints and describe their technical and structural characteristics as well as their strengths and weaknesses. This leads to the specification of a hybrid methodology as the preferred calculation approach. In the second part, we present the developed innovative hybrid land footprint method, consisting of a global land flow accounting and trade model capturing commodity flows in physical units to track embodied land along global supply chains. For non-food commodities the supply chains were complemented by an environmental input-output model. This method was used to calculate the cropland, grassland and forestland footprint of Germany and the EU. Finally, an overview of existing indicator systems for representing the environmental impacts of land use was provided and their complementary usage to extend area-based land footprints was discussed. A few of these complementary indicators were also quantified, most notably the deforestation footprint. The synthesis report closes with an overview of the thematic areas that need to be addressed in future research.
Keywords: Umweltschutz; Landwirtschaft; Flächennutzung; Flächenverbrauch; Indikator; Landnutzung; Nachhaltigkeit; Konsum; Berechnungsmethode